Quasianalytic functionals and projective descriptions - Bonet, José; Meise, Reinhold (Mathematica Scandinavica, 2004)
The topology of the weighted inductive limit of Fréchet spaces of entire functions in N variables which is obtained as the Fourier Laplace transform of the space of quasianalytic functionals on an open convex subset of R^N cannot be described by means of weighted sup-seminorms.